THE INFLUENCE OF FACILITIES, EMPLOYEE EMPOWERMENT, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN THE E-GOVERNMENT IMPLEMENTATION COMMUNICATION AND INFORMATION DIVISION OFFICE IN BATAM - Yusuda, Ahmad; Sabri, Sabri; Suyono, Suyono (Yayasan Education and Social Center, 2025)
The purpose of this study is to investigate the impact of facilities, employee empowerment, and job satisfaction on employee performance in the E-Government Implementation Division of the Batam City Communication and Informatics Office. In this investigation, employee performance is the dependent variable, while facilities, employee empowerment, and job satisfaction are independent variables. The research method is a descriptive, quantitative approach, with a population of 97 employees, all of whom were respondents via census methods. The research instrument in the form of a questionnaire has been tested for validity and reliability; all items are declared valid with r count > r table (0.1829) and significance <0.05, and all variables have Cronbach's Alpha values ​​above 0.60, namely facilities (0.832), employee empowerment (0.837), job satisfaction (0.873), and employee performance (0.782). The results of multiple linear regression analysis show the equation Y = 2.829 + 0.193X₁ + 0.451X₂ + 0.218X₃. The t-tests for each independent variable indicate a positive, significant effect on employee performance. In contrast, the F-test shows that all three variables have a significant simultaneous influence, with F = 42.386 > F table (2.72). The coefficient of determination (R²) of 0.594 indicates that these three variables explain 59.4% of the variation in employee performance. This study concludes that improving facilities, employee empowerment, and job satisfaction significantly optimize employee performance at the Batam City Communication and Informatics Office.